2013
DOI: 10.1021/jp4076367
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic Relaxation Enhancement Experiments: A Valuable Tool for the Characterization of Micellar Nanodevices

Abstract: Micellar incorporation of hydrophobic molecular receptors is a promising strategy to obtain efficient nanodevices that work in water. In order to fully evaluate the potential of this approach, information on the localization and orientation of the receptor inside the micelle are necessary. Systematic studies undertaken on a uranyl-salophen receptor incorporated into CTABr and CTACl micelles show that nuclear magnetic resonance paramagnetic relaxation enhancement (NMR-PRE) experiments are particularly suitable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
(79 reference statements)
0
11
0
Order By: Relevance
“…These concentrations are all well above the cmc of the surfactants and are comparable to those reported in previous studies. 19,20,33 Fluoride binding was monitored by UV-vis titrations for the receptors incorporated into the CTABr and CTACl micelles and Fig. 2 reports the data for the Receptor 2/CTABr system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These concentrations are all well above the cmc of the surfactants and are comparable to those reported in previous studies. 19,20,33 Fluoride binding was monitored by UV-vis titrations for the receptors incorporated into the CTABr and CTACl micelles and Fig. 2 reports the data for the Receptor 2/CTABr system.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported in the literature have shown that these experiments are particularly well suited to obtain information on the localisation and orientation of (bio)molecules inside micelles. 19,20,[34][35][36] Precise distance information can be obtained if a calibration procedure is first undertaken. 34,37 As we recently showed it is however possible to obtain reliable information on the localisation and orientation of receptors in micelles by simply comparing the PRE data obtained for the receptor protons with those of the surfactant protons of the micelles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Paramagnetic relaxation enhancements (PRE’s), which originates from electron-nucleus dipolar interactions, are a valuable alternative to obtain structural information by NMR, especially for large biomolecular systems 26 . The experiments reported in the present work rely on the use of the hexacyanochromate(III) anion as paramagnetic probe, which has been successfully exploited to characterize micellar incorporation, and focus on transverse relaxation enhancements that are easily detected in the 1D 1 H NMR spectrum as additional signal broadening 27 . Samples of RSV-loaded liposomes (100 mg/mL P90G, 2% w/w RSV) containing K 3 [Cr(CN) 6 ] were prepared in D 2 O following the same procedure as before (see Materials and Methods); the paramagnetic probe was thus present in both the outer and inner aqueous media of the liposomes.…”
Section: Resultsmentioning
confidence: 99%
“…However,e xamples of metallo-probes directly incorporated into micelles show that the major effect of micelles on receptors lacking ac avity,b eside their solubilization in aqueous media, is an enhanced affinity for lipophilic guests, which may be attributedt ot he hydrophobic effect. [24,[36][37][38][39] The interesting case that we have highlighted is that of au ranyl-salophen complexe mbedded in cationic micelles, [23,40] which binds the highly hydrophilic fluoridea nion with an increase in affinity of two orders of magnitude relative to the water-soluble version of the complex. [8] Electrostatic stabilization of the bound fluoride anion by the cationic micelle is probablyafactor in accountingf or this increased affinity.…”
Section: Resultsmentioning
confidence: 99%